Multiple Lines of Evidence Localize Signaling, Morphology, and Lipid Biosynthesis Machinery to the Mitochondrial Outer Membrane of Arabidopsis([W])([OA]) - Duncan, Owen (American Society of Plant Biologists, 2011)
The composition of the mitochondrial outer membrane is notoriously difficult to deduce by orthology to other organisms, and biochemical enrichments are inevitably contaminated with the closely associated inner mitochondrial membrane and endoplasmic reticulum. In order to identify novel proteins of the outer mitochondrial membrane in Arabidopsis (Arabidopsis thaliana), we integrated a quantitative mass spectrometry analysis of highly enriched and prefractionated samples with a number of confirmatory biochemical and cell biology approaches. This approach identified 42 proteins, 27 of which were novel, more than doubling the number of confirmed outer membrane proteins in plant mitochondria and suggesting novel functions for the plant outer mitochondrial membrane. The novel components identified included proteins that affected mitochondrial morphology and/or segregation, a protein that suggests the presence of bacterial type lipid A in the outer membrane, highly stress-inducible proteins, as well as proteins necessary for embryo development and several of unknown function. Additionally, proteins previously inferred via orthology to be present in other compartments, such as an NADH:cytochrome B5 reductase required for hydroxyl fatty acid accumulation in developing seeds, were shown to be located in the outer membrane. These results also revealed novel proteins, which may have evolved to fulfill plant-specific requirements of the mitochondrial outer membrane, and provide a basis for the future functional characterization of these proteins in the context of mitochondrial intracellular interaction.